Exploring the feasibility of establishing a core set of sexual, reproductive, maternal, newborn, child and adolescent health indicators in humanitarian settings: a multimethods, multicountry qualitative study protocol - Kobeissi, Loulou Hassan; Ashna, Manizha; Messier, Kassandre; Moran, Allisyn C; Say, Lale; Strong, Kathleen Louise; Foster, Angel (BMJ open, 2021)
IntroductionIn 2019, over 70 million people were forcibly displaced worldwide. Women and girls comprise nearly half of this population and are at heightened risk of negative sexual and reproductive health outcomes. With the collapse of health systems, reduced resources and increased vulnerabilities from displacement, there is a need to strengthen current practices and ensure the delivery of comprehensive sexual, reproductive, maternal, newborn, child and adolescent health (SRMNCAH) services. Recognising the need for consistency in data collection, analysis and use, the WHO developed a list of core SRMNCAH monitoring and evaluation indicators for services and outcomes in humanitarian settings. This research will explore the feasibility of collecting this core set of SRMNCAH indicators in displacement contexts.Methods and analysisWe will undertake a multimethods qualitative study in seven humanitarian settings: Afghanistan, Albania, Bangladesh, Cameroon, the Democratic Republic of the Congo, Iraq and Jordan. We selected sites that reflect diversity in geographic region, sociocultural characteristics, primary location(s) of displaced persons and nature and phase of the crisis. Our study consists of four components: key informant interviews, facility assessments, observational sessions at select facilities and focus group discussions with front-line healthcare personnel. We will analyse our data using descriptive statistics and for content and themes. We will begin by analysing data from each setting separately and will then combine these data to explore concordant and discordant results, triangulate findings and develop global recommendations.Ethics and disseminationThe University of Ottawa’s Research Ethics Board and the Research Project Review Panel (RP 2) of the World Health Organization-Department of Sexual and Reproductive Health as well as local IRBs of PIs’ research institutions reviewed and approved this protocol. We intend to disseminate findings through workshops at the WHO country, regional and headquarter levels, as well as through local, national and international conferences, workshops, peer-reviewed publications, and reports.